open import Cat.Diagram.Initial open import Cat.Instances.Comma open import Cat.Prelude import Cat.Functor.Reasoning as Func import Cat.Reasoning module Cat.Functor.Adjoint where

# Adjoint functors🔗

Category theory is, in general, the study of how things can be related. For instance, structures at the level of sets (e.g. the collection of natural numbers) are often interestingly related by propositions (i.e. the proposition $x \le y$). Structures at the level of groupoids (e.g. the collection of all sets) are interestingly related by sets (i.e. the set of maps $x \to y$). Going further, we have structures at the level of 2-groupoids, which could be given an interesting *category* of relations, etc.

A particularly important relationship is, of course, “sameness”. Going up the ladder of category number, we have equality at the (-1)-level, isomorphism at the 0-level, and what’s generally referred to as “equivalence” at higher levels. It’s often interesting to weaken these relations, by making some components directed: This starts at the level of categories, where “directing” an equivalence gives us the concept of **adjunction**.

An *equivalence of categories* between $\ca{C}$ and $\ca{D}$ is given by a pair of functors $L : \ca{C} \leftrightarrows \ca{D} : R$, equipped with natural *isomorphisms* $\eta : \id{Id} \cong (R \circ L)$ (the “unit”) and $\eps : (L \circ R) \cong \id{Id}$ (the “counit”). We still want the correspondence to be bidirectional, so we can’t change the types of $R$, $L$; What we *can* do is weaken the natural isomorphisms to natural *transformations*. The data of an **adjunction** starts as such:

record _⊣_ (L : Functor C D) (R : Functor D C) : Type (adj-level C D) where private module C = Precategory C module D = Precategory D field unit : Id => (R F∘ L) counit : (L F∘ R) => Id module unit = _=>_ unit module counit = _=>_ counit renaming (η to ε)

Unfortunately, the data that we have here is not particularly coherent. The unit and counit let us introduce $R\circ L$ and eliminate $L\circ R$ in a composition, which gives us two ways of mapping $L \To L$. One is the identity, and the other is going through the unit: $L \To L\circ R\circ L \To L$ (the situation with $R$ is symmetric). We must impose further equations on the natural transformations to make sure these match:

field zig : ∀ {A} → counit.ε (F₀ L A) D.∘ F₁ L (unit.η A) ≡ D.id zag : ∀ {B} → F₁ R (counit.ε B) C.∘ unit.η (F₀ R B) ≡ C.id infixr 15 _⊣_

These are called “triangle identities” because of the shape they have as commutative diagrams:

# Universal morphisms🔗

Another perspective on adjoint functors is given by finding “most efficient solutions” to the “problem” posed by a functor. For instance, the (ff) inclusion of prosets into strict precategories poses the problem of turning a precategory into a proset. While this can’t be done in a 1:1 way (precategories are strictly more general than prosets), we *can* still ponder whether there is some “most efficient” way to turn a category into a proset.

While we can’t directly consider maps from precategories to proset, we *can* consider maps from precategories to the inclusion of a proset; Let us write $\ca{C}$ for a generic precategory, $\ca{P}$ for a generic proset, and $U(\ca{P})$ for $\ca{P}$ considered as a precategory. Any functor $\ca{C} \to U(\ca{P})$ can be seen as “a way to turn $\ca{C}$ into a proset”, but not all of these can be the “most efficient” way. In fact, there is a vast sea of uninteresting ways to turn a precategory into a proset: turn them all into the terminal proset!

A “most efficient” solution, then, would be one through which all others factor. A “universal” way of turning a strict precategory into a proset: A **universal morphism** from $\ca{C}$ to $U$. The way we think about universal morphisms (reusing the same variables) is as initial objects in the comma category $\ca{C} \swarrow U$, where that category is conceptualised as being “the category of maps from $\ca{C}$ to $U$”.

Universal-morphism : C.Ob → Functor D C → Type _ Universal-morphism X R = Initial (X ↙ R)

Abstracting away, suppose that $R : D \to C$ has universal morphisms for every object of $C$. To show the correspondence between these two ideas of adjunction, we show that this assignment extends to a functor $L : C \to D$, with $L \dashv R$ as defined above.

## Defining the L🔗

We first show that the assignment of universal morphisms restricts to a functorial assignment $L : C \to D$. Recall that an object in $X \swarrow R$ is given by a codomain $y$ and a map $X \to R(y)$. We define $L_0(x)$ to be the codomain of the universal morphism:

L₀ : C.Ob → D.Ob L₀ x = universal-map-for x .bot .↓Obj.y L₀′ : (c : C.Ob) → C.Hom c (R.₀ (L₀ c)) L₀′ x = universal-map-for x .bot .map

Given an arrow $a \to b$ in $\ca{C}$, we can send it to a uniquely-determined *object* in $a \swarrow R$: We take the universal arrow assigned to $b$ (an object of $b \swarrow R$), and precompose with $a$. This object will then serve as the domain of the morphism part of $L$, which is given by the unique assignment arrows out of the initial object in $a \swarrow R$ (see lift↓ below).

private to-ob : ∀ {a b} → C.Hom a b → (a ↙ R) .Precategory.Ob to-ob {a} {b} h = record { map = L₀′ b C.∘ h } lift↓ : ∀ {x y} (g : C.Hom x y) → Precategory.Hom (x ↙ R) (universal-map-for x .bot) (to-ob g) lift↓ {x} {y} g = ¡ (universal-map-for x) {to-ob g} L₁ : ∀ {a b} → C.Hom a b → D.Hom (L₀ a) (L₀ b) L₁ {a} {b} x = lift↓ x .β

## It now suffices to show the functor identities hold for L₁. They follow essentially from the uniqueness of maps out of an initial object.

private abstract L-id : ∀ {a} → L₁ (C.id {a}) ≡ D.id {L₀ a} L-id {a} = ap β (¡-unique (universal-map-for a) (record { sq = C.elimr refl ·· C.elimr refl ·· sym (C.eliml R.F-id) })) lemma : ∀ {x y z} (f : C.Hom y z) (g : C.Hom x y) → R.₁ (L₁ f D.∘ L₁ g) C.∘ (L₀′ x) ≡ to-ob (f C.∘ g) .map C.∘ C.id lemma {x} {y} {z} f g = R.₁ (lift↓ f .β D.∘ lift↓ g .β) C.∘ (L₀′ x) ≡⟨ C.pushl (R.F-∘ _ _) ⟩≡ R.₁ (lift↓ f .β) C.∘ R.₁ (lift↓ g .β) C.∘ (L₀′ x) ≡⟨ ap (R.₁ (lift↓ f .β) C.∘_) (sym (lift↓ g .↓Hom.sq) ∙ C.idr _) ⟩≡ R.₁ (lift↓ f .β) C.∘ L₀′ y C.∘ g ≡⟨ C.extendl (sym (lift↓ f .↓Hom.sq) ∙ C.idr _) ⟩≡ L₀′ z C.∘ f C.∘ g ≡˘⟨ C.idr _ ⟩≡˘ to-ob (f C.∘ g) .map C.∘ C.id ∎ L-∘ : ∀ {x y z} (f : C.Hom y z) (g : C.Hom x y) → L₁ (f C.∘ g) ≡ L₁ f D.∘ L₁ g L-∘ f g = ap β (¡-unique (universal-map-for _) (record { sq = sym (lemma f g) }))

That out of the way, we have our $L$ functor. We now have to show that it defines a left adjoint to the $R$ we started with.

universal-maps→L : Functor C D universal-maps→L .F₀ = L₀ universal-maps→L .F₁ = L₁ universal-maps→L .F-id = L-id universal-maps→L .F-∘ = L-∘

## Building the adjunction🔗

We now prove that $L \dashv R$, which, recall, means giving natural transformations $\eta : \id{Id} \To (R F\circ L)$ (the *adjunction unit*) and $\eps : (L \circ R) \To \id{Id}$ (the *adjunction counit*). We begin with the counit, since that’s more involved.

The construction begins by defining a function mapd which sends each object of $\ca{C}$ to the initial object in $x \swarrow R$. Note that this is the same as L₀, but returning the entire object rather than a part of it.

private mapd : ∀ (x : C.Ob) → Ob (x ↙ R) mapd x = universal-map-for x .bot

Now for an object $x : \ca{D}$, we have $R(x) : \ca{C}$, so by the assumption that $R$ has a collection of universal objects, the comma category $R(x) \swarrow R$ has an initial object; Let us write that object as $(L(R(x)), !)$ — recall that here, $! : R(x) \to RLR(x)$.

This means, in particular, that for any other object $(y, f)$ (with $y \in \ca{D}$ and $f : R(x) \to R(y)$ in $\ca{C}$), there is a unique map $\id{mapd}(x) \to (y, f)$, which breaks down as a map $\beta : L(R(x)) \to y$ such that the square below commutes.

ε : ∀ (x : D.Ob) → Hom (R.₀ x ↙ R) (mapd (R.₀ x)) _ ε x = Initial.¡ (universal-map-for (R.₀ x)) {x = record { y = x ; map = C.id }}

The magic trick is that, if we pick $(x, \id{id})$ as the object of $R(x)\swarrow R$ to map into, then $\beta$ in the diagram above must be $LR(x) \to x$! We choose this map as our adjunction counit. A tedious calculation shows that this assignment is natural, essentially because $\beta$ is unique.

universal-maps→L⊣R : universal-maps→L ⊣ R universal-maps→L⊣R .counit .η x = ε x .↓Hom.β universal-maps→L⊣R .counit .is-natural x y f = ap ↓Hom.β ( ¡-unique₂ (universal-map-for (R.₀ x)) {record { map = R.₁ f }} (record { sq = R.₁ f C.∘ C.id ≡⟨ C.idr _ ⟩≡ R.₁ f ≡˘⟨ C.cancell (sym (ε y .↓Hom.sq) ∙ C.idr _) ⟩≡˘ R.₁ (ε y .β) C.∘ _ C.∘ R.₁ f ≡˘⟨ ap₂ C._∘_ refl (sym (lift↓ (R.₁ f) .↓Hom.sq) ∙ C.idr _) ⟩≡˘ R.₁ (ε y .β) C.∘ R.₁ (L₁ (R.₁ f)) C.∘ mapd (R.₀ x) .map ≡⟨ C.pulll (sym (R.F-∘ _ _)) ⟩≡ R.₁ (ε y .β D.∘ L₁ (R.₁ f)) C.∘ mapd (R.₀ x) .map ∎ }) (record { sq = R.₁ f C.∘ C.id ≡˘⟨ ap (R.₁ f C.∘_) (sym (ε x .↓Hom.sq) ∙ C.idr _) ⟩≡˘ R.₁ f C.∘ R.₁ (ε x .β) C.∘ mapd (R.₀ x) .map ≡⟨ C.pulll (sym (R.F-∘ _ _)) ⟩≡ R.₁ (f D.∘ ε x .β) C.∘ mapd (R.₀ x) .map ∎ }))

For the adjunction unit, the situation is a lot easier. Recall that we *defined* $L(x)$ on objects (L₀) to be the codomain part of the initial object of $x \swarrow R$; The *map* part of that object then gives us a natural family of morphisms $x \to R(L(x))$. By definition. It’s so “by definition” that Agda can figure out the components by itself:

universal-maps→L⊣R .unit .η x = _ universal-maps→L⊣R .unit .is-natural x y f = sym (C.idr _) ∙ lift↓ f .↓Hom.sq

If you think back to the adjunction counit, you’ll recall that it satisfied a triangle that looks like the one below, and that the top map (the map component of the initial object) is what we defined the adjunction unit to be, so.. It’s zag.

universal-maps→L⊣R .zag {x} = sym (ε x .↓Hom.sq) ∙ C.idr _

The other triangle identity is slightly more annoying, but it works just as well. It follows from the uniqueness of maps out of the initial object:

universal-maps→L⊣R .zig {x} = ap ↓Hom.β ( ¡-unique₂ (universal-map-for x) {record { map = α }} (record { sq = α C.∘ C.id ≡⟨ C.idr _ ⟩≡ α ≡˘⟨ C.cancell (sym (ε (L₀ x) .↓Hom.sq) ∙ C.idr _) ⟩≡˘ R.₁ _ C.∘ _ C.∘ α ≡˘⟨ C.pullr (sym (lift↓ α .↓Hom.sq) ∙ C.idr _) ⟩≡˘ (R.₁ _ C.∘ R.₁ (F₁ L α)) C.∘ α ≡˘⟨ ap (C._∘ α) (R.F-∘ _ _) ⟩≡˘ R.₁ (_ D.∘ F₁ L α) C.∘ α ∎ }) (record { sq = C.id-comm ∙ ap (C._∘ _) (sym R.F-id) }) ) where α = L₀′ x L = universal-maps→L

## From an adjunction🔗

To finish the correspondence, we show that any (left) adjoint functor $L \dashv R$ defines a system of universal arrows $- \swarrow R$; This means that, not only does a “universal way of solving $R$” *give* a left adjoint to $R$, it *is* a left adjoint to $R$.

So, given an object $x \in \ca{C}$, we must find an object $y$ and a universal map $x \to R(y)$. Recall that, in the previous section, we constructed the left adjoint $L$’s action on objects by using our system of universal arrows; Symetrically, in this section, we take the codomain to be $y = L(x)$. We must then find an arrow $x \to RLx$, but this is exactly the adjunction unit $\eta$!

L⊣R→map-to-R : ∀ x → Precategory.Ob (x ↙ R) L⊣R→map-to-R x .↓Obj.x = tt L⊣R→map-to-R x .↓Obj.y = L.₀ x L⊣R→map-to-R x .↓Obj.map = adj.unit.η _

We must now show that the unit $\eta$ is universal among the pairs $(y, f)$, with $f$ a map $x \to R(y)$. Recall that for our object $(Lx, \eta)$ to be initial, we must find an arrow $(y, f) \to (Lx, \eta)$, and prove that this is the only possible such arrow; And that morphisms in the comma category $x \swarrow R$ break down as maps $g : Lx \to y$ such that the triangle below commutes:

We can actually read off the map $g$ pretty directly from the diagram: It must be a map $Lx \to y$, but we’ve been given a map $LRx \to x$ (the adjunction counit) and a map $x \to Ry$; We may then take our $g$ to be the composite

$Lx \to LRy \to y$

L⊣R→map-to-R-is-initial : ∀ x → is-initial (x ↙ R) (L⊣R→map-to-R x) L⊣R→map-to-R-is-initial x other-map .centre .↓Hom.α = tt L⊣R→map-to-R-is-initial x other-map .centre .↓Hom.β = adj.counit.ε _ D.∘ L.₁ (other-map .↓Obj.map) L⊣R→map-to-R-is-initial x other-map .centre .↓Hom.sq = sym ( R.₁ (adj.counit.ε _ D.∘ L.₁ om.map) C.∘ adj.unit.η _ ≡⟨ ap₂ C._∘_ (R.F-∘ _ _) refl ∙ sym (C.assoc _ _ _) ⟩≡ R.₁ (adj.counit.ε _) C.∘ R.₁ (L.₁ om.map) C.∘ adj.unit.η _ ≡˘⟨ C.refl⟩∘⟨ adj.unit.is-natural _ _ _ ⟩≡˘ (R.₁ (adj.counit.ε _) C.∘ adj.unit.η _ C.∘ om.map) ≡⟨ C.cancell adj.zag ⟩≡ om.map ≡⟨ sym (C.idr _) ⟩≡ om.map C.∘ C.id ∎ ) where module om = ↓Obj other-map

Checking that the triangle above commutes is a routine application of naturality and the triangle identities; The same is true for proving that the map $g$ above is unique.

L⊣R→map-to-R-is-initial x other-map .paths y = ↓Hom-path _ _ refl ( adj.counit.ε _ D.∘ L.₁ om.map ≡⟨ D.refl⟩∘⟨ L.expand (sym (C.idr _) ∙ y .↓Hom.sq) ⟩≡ adj.counit.ε _ D.∘ L.₁ (R.₁ y.β) D.∘ L.₁ (adj.unit.η _) ≡⟨ D.pulll (adj.counit.is-natural _ _ _) ⟩≡ -- nvmd (y.β D.∘ adj.counit.ε _) D.∘ L.₁ (adj.unit.η _) ≡⟨ D.cancelr adj.zig ⟩≡ y.β ∎ ) where module om = ↓Obj other-map module y = ↓Hom y

Hence, we can safely say that having a functor $L$ and an adjunction $L \dashv R$ is the same thing as having a functor $R$ and a system of universal arrows into $R$:

L⊣R→universal-maps : ∀ x → Universal-morphism x R L⊣R→universal-maps x .Initial.bot = L⊣R→map-to-R x L⊣R→universal-maps x .Initial.has⊥ = L⊣R→map-to-R-is-initial x

# Adjuncts🔗

Another view on adjunctions, one which is productive when thinking about adjoint *endo*functors $L \dashv R$, is the concept of *adjuncts*. Any pair of natural transformations *typed like* a unit and counit allow you to pass between the Hom-sets $\hom(La,b)$ and $\hom(a,Rb)$, by composing the functorial action of $L$ (resp $R$) with the natural transformations:

L-adjunct : ∀ {a b} → D.Hom (L.₀ a) b → C.Hom a (R.₀ b) L-adjunct f = R.₁ f C.∘ adj.unit.η _ R-adjunct : ∀ {a b} → C.Hom a (R.₀ b) → D.Hom (L.₀ a) b R-adjunct f = adj.counit.ε _ D.∘ L.₁ f

The important part that the actual data of an adjunction gets you is these functions are inverse *equivalences* between the hom-sets $\hom(La,b) \cong \hom(a,Rb)$.

L-R-adjunct : ∀ {a b} → is-right-inverse (R-adjunct {a} {b}) L-adjunct L-R-adjunct f = R.₁ (adj.counit.ε _ D.∘ L.₁ f) C.∘ adj.unit.η _ ≡⟨ R.pushl refl ⟩≡ R.₁ (adj.counit.ε _) C.∘ R.₁ (L.₁ f) C.∘ adj.unit.η _ ≡˘⟨ C.refl⟩∘⟨ adj.unit.is-natural _ _ _ ⟩≡˘ R.₁ (adj.counit.ε _) C.∘ adj.unit.η _ C.∘ f ≡⟨ C.cancell adj.zag ⟩≡ f ∎ R-L-adjunct : ∀ {a b} → is-left-inverse (R-adjunct {a} {b}) L-adjunct R-L-adjunct f = adj.counit.ε _ D.∘ L.₁ (R.₁ f C.∘ adj.unit.η _) ≡⟨ D.refl⟩∘⟨ L.F-∘ _ _ ⟩≡ adj.counit.ε _ D.∘ L.₁ (R.₁ f) D.∘ L.₁ (adj.unit.η _) ≡⟨ D.extendl (adj.counit.is-natural _ _ _) ⟩≡ f D.∘ adj.counit.ε _ D.∘ L.₁ (adj.unit.η _) ≡⟨ D.elimr adj.zig ⟩≡ f ∎ L-adjunct-is-equiv : ∀ {a b} → is-equiv (L-adjunct {a} {b}) L-adjunct-is-equiv = is-iso→is-equiv (iso R-adjunct L-R-adjunct R-L-adjunct) R-adjunct-is-equiv : ∀ {a b} → is-equiv (R-adjunct {a} {b}) R-adjunct-is-equiv = is-iso→is-equiv (iso L-adjunct R-L-adjunct L-R-adjunct)